APLIKASI MANAJEMEN QOLBU DI PONDOK PESANTREN DAARUT TAUHID BANDUNG - Evita Yuliatul Wahidah (Nurul Jadid University, 2018)
Qalbu Management is a concept of Islamic life guidance that was initiated by Daarut Tauhid Leadership School of Bandung, KH Abdullah Gymnastiar (Aa Gym), which teaches a new concept of Shiva Islam. Qolbu Management offers to invite people to understand the heart or heart, self, in order to want and be able to control themselves after understanding who is really himself. So the concept of Qolbu Management is a consciousness that is generated on his own consciousness to make his life better and always be in the pleasure of Allah. In this discussion will explore the meaning of qolbu, its parts, and the classification of qolbu. In addition, the concept of qolbu management and management mode qalbu as an effort to get to know the potential and liver problems to further develop its ability optimally and eliminate problems arising from mismanagement. Portrait of Pondok Pesantren Daarut Tahuid is also presented, as the first laboratory of qolbu management. Manfaaat qalbu management is also the main focus, because qalbu Management can be applied to overcome the problem of non-infectious disease which one of the risk factor of the disease is behavior.